Estudo do pré-natal de risco habitual como estratégia para redução da mortalidade materna - BOUÉRES, Maria de Fátima Portela Silva (2019)
The usual risk prenatal care is characterized by the care provided by the family health team to the prenatal care of pregnant women without risk factors for maternal-perinatal health problems or presenting risk factors that can be conducted in Primary Care. The objective of this study was to study prenatal risk as a strategy to reduce maternal mortality. This is a descriptive study with a quantitative approach, carried out with senior professionals working in the Primary Health Care (PHC) involved in the prenatal care of two basic health units. An authorized modified questionnaire from the Federal University of Pelotas, Rio Grande do Sul, containing open and closed questions regarding the characterization of participants and prenatal habitual risk was applied. The data were collected in the months of April and May 2019 and analyzed through the Epi-Info and Excel programs. The results showed that 72.7% of the professionals are female and 27.3% are male, 45.45% are doctors, 45.45% are nurses and 9.2% are dental surgeons. The time of performance in the Primary Health Care (PHC) ranged from 9.2% with up to 5 years of activity to 63.5% over 10 years of operation. As to the main cause of maternal mortality, 54,5% reported inadequate prenatal care, 9,1% reported lack of protocol and 18,2% delivery care, and 9,1% reported that it was hypertension and bleeding. About 72.7% of the professionals said they did it, and 27.3% stated that they did not carry out these activities. Regarding whether the pregnant woman leaves UBS with the next scheduled appointment, 81.8% said yes and 18.2%, which they do not. The study indicates the need for improvements in prenatal care at usual risk, qualifying the health team and implementing actions directed at pregnant women and partnerships through education, promotion and prevention in health.